The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Logic, Construction, Computation 2012
DOI: 10.1515/9783110324921.343
|View full text |Cite
|
Sign up to set email alerts
|

Another Unique Weak König’s Lemma WKL!!

Abstract: For Helmut Schwichtenberg, with respect and appreciation for his encouragement and friendship.In [2] J. Berger and Ishihara proved, via a circle of informal implications involving countable choice, that Brouwer's Fan Theorem for detachable bars on the binary fan is equivalent in Bishop's sense to various principles including a version WKL! of Weak König's Lemma with a strong effective uniqueness hypothesis. Schwichtenberg [9] proved the equivalence directly and formalized his proof in Minlog. We verify that hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Notice that our notion of WKL!!! differs only slightly from the one of J. Moschovakis, who first considered it [97]. In her version, named WKL!…”
Section: (Wkl!!!)mentioning
confidence: 88%
“…Notice that our notion of WKL!!! differs only slightly from the one of J. Moschovakis, who first considered it [97]. In her version, named WKL!…”
Section: (Wkl!!!)mentioning
confidence: 88%
“…In [7], equivalents are given for what is there called FAN and WKL, although their FAN is actually D-FAN, and it is at least asked how much stronger WKL is than FAN. The one proof we have been able to find of some fan theorem not implying WKL is in [19], where once again the fan principle used is D-FAN. For what it's worth, that argument, like ours, uses relative realizability [8], albeit with K 2 realizability.…”
Section: Fan and Wklmentioning
confidence: 99%
“…In this paper, we decompose weak König’s lemma with a uniqueness hypothesis from Moschovakis [3], abbreviated WKL!!, into logical and function–existence principles in a recent framework of CRM.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Moschovakis [3] introduced another version of unique weak König’s lemma WKL!! where the uniqueness hypothesis is defined in a naive way: any two paths through a given infinite binary tree are the same (see (2.3) for the precise definition). Then she showed that WKL!! can be decomposed into the Π10-fragment of De Morgan’s law (under the name of normalMP from Ishihara [12]) and the double negated variant of WKL (see [3, Section 4]), and also that WKL!! lies strictly between WKL! and WKL (see [3, Section 5]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation